SOCIAL THEORIES and ON WOMEN - Veda BİLİCAN GÖKKAYA (Fırat University, 2019)
Concept of woman which has a very important place in the construction of a society is a field of problem that must be searched, studied and worked out. Women who carry both the past, present and the future of the society they are living inhave still been the matter of discussion with their feeling lowly, early marriages, poorness and deprivations and social inequalities. As Weeden (1997) stated, this problem in which the power relation where profits of women are subjected to those of men that is to say patriarchal discourse dominates is a problem of universal dimension taken from past up to present. Perspective of the social theories also take an important placein this field of problem where the discussions continue / are continued. Each of the theories (Functionalist Theory, Conflict Theory, Phenomenology, Symbolic Interactionist Theory, Rational Choice Theory, Body Theory, Feminist Theory andModernization Theory) which asserts different information and arguments on the definition position and role of women in the socio-cultural and economic structure in the society is in depth of a book, this study only has the characteristics ofbeing an introduction. In this study, the effects of social theories which are among the cornerstones of science for the explanation of social realities on woman problem which is a social problem will be discussed. In this study which has the characteristics of a compilation, articles, books and magazines related to the study were scanned appealing to documentary observation and in the following process the valid data have been collected under the suitable titles and interpreted and reported.